The reincorporation of Tacna from the perspective of "El Pacífico" in 1929 - Chura Bárcena, Abelardo Máximo (2023)
The written press plays a crucial role, which is why this article revolves particularly around the newspaper "El Pacífico". The War of the Pacific, the Occupation and the Process of Reincorporation of Tacna are the junctures in which the newspaper is linked. Its search for information through qualitative techniques cooperated in the analysis until 1929. The paper's discourses on political views of yesteryear and today are part of that analysis. Throughout the text, the complex and multifaceted roles of the press in the construction of national narratives and in the documentation of historical events emerge.